Multi-objective optimization problems : concepts and self-adaptive parameters with mathematical and engineering applications /: concepts and self-adaptive parameters with mathematical and engineering applications. ([2017]) - Lobato, Fran Sérgio; Jr, Steffen, Valder
No abstract available